Analysis of Dynamic Response Mechanism of Roadway Bolt - Qinjian Zhan; Xigui Zheng; Niaz Muhammad Shahani; Xiao Tan; Tao Li; Jiping Du (Advances in Civil Engineering)
This work elucidates dynamic control equations of the anchoring system and the derivation of displacement equations and corresponding vibration modes. Furthermore, the anchoring system is found to be composed of three different vibration modes: (1) when ω < (k1/ρ1A1)1/2, the vibration mode of the anchoring section is an exponential function; (2) when ω = (k1/ρ1A1)1/2, the vibration mode of the anchoring section is a parabolic function; (3) when ω >  (k1/ρ1A1)1/2, the vibration mode of the anchoring section is a trigonometric function, while all the free sections are trigonometric functions. With an increase of frequency, the amplitude of the bolt exhibits multipeak distribution characteristics and an intermittent amplification phenomenon. When the frequency reaches a certain value, the bolt of the free section exhibits only the amplified state. Under dynamic load, the amplitude of the bolt increases from end of bolt to the maximum in the root. On the other hand, when the frequency is low, the peak position of the roof bolt is stable, and the excitation wave component is the main influencing factor of the peak value of axial force at the root of the bolt, independent of frequency. When the frequency is relatively high, the peak value of the axial force is stable at the interface, and the higher the frequency, the greater the peak value of axial force. Axial force of the bolt has responded strongly to the frequency at the interface, and the farther away from the interface, the weaker the response.